Menjadikan Manajemen sebagai Paradigma Pembangunan dalam Mewujudkan Good Governance - - Muqodim (Unisia, 2004)
One of main causes for multicrisis in Indonesia are mismanagement and moral hazard problem in every sectors. Political situation and economy is a two sides which linked each other. So far, executives in government mostly see politics and economy as the effort to gain power for individuals or groups, fully ignoring the essential task for manager to maintain the country using good management principles which will enable to rise sustainable value of creation. The core conditions of the success of nation building is through well understanding toward the proposed goal, i.e. independency, developed, and welfare in national life. The only way to attain is to maintain this country by utilizing good management.